(untitled) (Scientific Journal for Publishing in Health Research and Technology, 2025)
This study assessed the efficiency of the Desalination Plant at the Libyan Iron and Steel Company (LISCO) in Misrata in salt rejection. This was carried out by collecting samples of the feed and product water from the plant every three days for a full month, after which they were transported to the Agricultural Research Laboratory in the Ghiran area of Misrata city. Tests were conducted on all samples under study, and the average monthly measurements of Total Dissolved Solids (TDS), Electrical Conductivity (EC), and pH for both feed and product water were calculated. The average measurements for Electrical Conductivity (EC) were found to be within the permissible limits of Libyan specifications, with the plant’s efficiency for these measurements reaching 63.47%. The plant’s efficiency for pH measurements was 23.34%, which is lower than the minimum limit allowed by Libyan specifications. Meanwhile, the plant’s efficiency for Total Dissolved Solids (TDS) measurements reached an excellent 99.96%. Overall, the plant’s efficiency has declined, especially regarding EC levels, compared to previous years, particularly those close to its inauguration.